Genetic Conditions Affecting the Skeleton Congenital, Idiopathic Scoliosis and Arthrogryposis - Giampietro, Philip; Hadley-Miller, Nancy; Raggio, Cathy L. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this Special Issue of Genes entitled "Genetic Conditions Affecting the Skeleton: Congenital, Idiopathic Scoliosis and Arthrogryposis", evidence is presented that suggests that congenital, idiopathic scoliosis, and arthrogryposis share similar overlapping, but also distinct, etiopathogenic mechanisms, including connective tissue and neuromuscular mechanisms. Congenital scoliosis (CS) is defined by the presence of an abnormal spinal curvature, due to an underlying vertebral bony malformation (VM). Idiopathic scoliosis (IS) is defined by the presence of an abnormal structural spinal curvature of ≥10 degrees in the sagittal plane, in the absence of an underlying VM. Arthrogryposis is defined by the presence of congenital contractures in two or more joints of the appendicular skeleton. All three conditions have complex genetic causes. This Special Issue highlights the complex nature of these conditions and current concepts in our approach to better understand their genetics.